Community Support Groups and Home-Based Care among Persons Living with HIV and AIDS in Lira District, Uganda - Zamaradi Auma; Gilbert Obici; David Mwesigwa (Goodwood Publishing, 2022)
Purpose: This study investigated the contribution of Community support groups on Home based care to Persons Living with HIV in Lira District. Research Methodology: We adopted a cross-sectional research design among a sample of 226 respondents. Using both the Self-Administered Questionnaires and an Interview Guide. Results: The findings suggested that Community support groups (?=4.959, SD=0.5393) help in enhancing home-based care for PLHIV in Lira District. Further, Community support groups had a significant effect on Adherence to ART (?=0.641, P<0.05), Nutrition support (?=0.581, P<0.05), and Palliative care (?=0.638, P<0.05). Limitations: This study covered only one district in the entire Lango sub-region yet if more districts were included, possibly the outcomes would have been different. Contribution: This study contributes empirical evidence of the association between Community support groups and home-based care to PLHIV in Lira District. Therefore, for improved home-based care for PLHIV, stakeholders are encouraged to mobilize local communities to form Community support groups so that they can be able to offer support to PLHIV. Practical implication: The study contributes to practice since HBC CSG can be used as a tool for improving the level of palliative care among the PLHIV in the local community given that the care for PLHIV has greatly moved away from the hospital-based to home-based. Novelty: Studies on Community support groups are still limited since much of the literature originates from other parts save for Uganda and it is worse for Lira district.